Ideologi Pemanah berkuda Tradisional - Fajri, Rahmat; Muchtar, Aflatun; Julizun, Alfi (TSAQAFAH, 2025)
This study discusses the ideology applied by traditional Horsebow archers in South Sumatra, specifically within the Perkumpulan Pemanah Berkuda Indonesia (Perdana). The aim of this research is to understand the ideological concepts held by the traditional archery community, analyze the training processes they undergo, and investigate their influence and contributions to strengthening collective identity and enhancing the performance of its members. Using an ethnographic approach, this research reveals the significant role of the Horsebow archer ideology in fortifying local cultural roots, expanding influence, and achieving achievements at national and international levels. This traditional archery practice not only strengthens the Islamic cultural heritage but also enhances the technical skills of community members while enriching their collective identity. The dedication of the younger generation in preserving traditional practices and applying these ideological values has proven to result in achievements, build strong social bonds, and make a significant contribution to preserving religious and national values. The ideology upheld by the Horsebow archers also plays a role in strengthening national identity through sport and tradition, while celebrating cultural diversity in Indonesia.